Benziporphyrins, a unique platform for exploring the aromatic characteristics of porphyrinoid systems. Issue 29 (7th August 2015) - Lash, Timothy D.
<x xml:space="preserve">Abstract</x> Benziporphyrins and related systems exhibit a wide range of properties and may possess nonaromatic, strongly aromatic or even antiaromatic characteristics.